2020
DOI: 10.3390/biom10040632
|View full text |Cite
|
Sign up to set email alerts
|

Ceramides Profile Identifies Patients with More Advanced Stages of Colorectal Cancer

Abstract: Much attention is paid to different sphingolipid pathways because of their possible use in diagnostics and treatment. However, the activity status and significance of ceramide pathways in colorectal cancer are still unclear. We analyzed colorectal cancer patients to evaluate sphingolipid profiles in the blood, colorectal cancer (CRC) tissues, and healthy surrounding colorectal tissues of the same patient, simultaneously, using liquid chromatography coupled with triple quadrupole mass spectrometry. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…In current study, the difference in total Cer amounts between tumor and tumor adjacent tissue (Fig. 1) are in agreement with previous reports of elevated Cer synthases expression levels [54], as well as total Cer content in CRC tissues [29,53].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In current study, the difference in total Cer amounts between tumor and tumor adjacent tissue (Fig. 1) are in agreement with previous reports of elevated Cer synthases expression levels [54], as well as total Cer content in CRC tissues [29,53].…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that they regulate ion channels, which may constitute the mechanism underlying the regulation of cell proliferation [52]. Likewise, the exact nature of sphingolipid metabolism in carcinogenic processes is not yet clear, but seems to be dependent on acyl-chain composition [53]. In current study, the difference in total Cer amounts between tumor and tumor adjacent tissue (Fig.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Interestingly, an investigation on colorectal cancer (CRC) tissue has suggested that CRC shows increased amounts of S1P, Sph, and C14-Cer and markedly reduced amounts of C18-Cer and C20-Cer. The circulating contents of C16:0-Cer, C18:1-Cer, C20-Cer, and C24:1-Cer in more advanced CRC were higher than those in early lesions ( 32 ). These results suggest that early lesions can be distinguished from advanced CRC through the combined determination of the plasma concentrations of several ceramides.…”
Section: The Value Of Sphingolipid Metabolism In Cancermentioning
confidence: 87%
“…Sphingolipids such as ceramide, sphingosine, sphingosine-1-phosphate (S1P), and ceramide-1-phosphate (C1P) play important roles in cell signaling events, including apoptosis, differentiation, regulation of receptor kinase and phospholipase activities. 11 Although the implication and function of sphingolipids in cell signaling has been highly controversial, accumulating evidence suggests that CRC in different stages exhibits alterations in sphingolipids and their metabolizing enzymes, either in the serum or the tumor, 12–14 and several studies have found that dietary sphingolipids or the gut microbiome influence CRC carcinogenesis via alterations in sphingolipids. 15…”
Section: Introductionmentioning
confidence: 99%